An evaluation of Potts' aortopulmonary shunt for palliation of cyanotic heart disease. - Daniel, F J (1976)
The results of 28 Potts' aortopulmonary shunts created for the relief of cyanotic heart disease are reviewed in this study. The shunt gave excellent symptomatic relief, but the incidence of immediate and late complications is high. Regular follow-up of patients is mandatory to detect evidence of increasing pulmonary vascular disease and to under take corrective surgery whenever feasible before its occurrence. Although Potts' anastomosis has been largely replaced by alternative shunt procedures, there may still be a place for its application in selected situations. Only a few problems were encountered at the time of closure of the shunt in 11 patients during corrective surgery using a transpulmonary technique and hypothermia with circulatory arrest.